Efficiency of the special systems regarding the overdentures retention on implants - Bogdan Mihai Gălbinaşu; Vlad Vasilescu; Ion Pătraşcu (Amaltea Medical Publishing House, 2019)
Restoring of the fully edentulous patients remains one of the great challenges for the dental practitioners, who seek solutions for continuous improvement of the prosthetic methods, starting from understanding the differences between the support offered by the root and the implant to the prosthetic restoration. At the moment, there are many types and systems that improve the connection between the base of the prosthesis and the implant, but the information în the literature regarding their performance îs insufficient. The paper presents a synthesis of the information from the specialized literature regarding the use and the performance of special systems used with overdentures on implants aş well aş the results of a study performed on a sample of 25 patients with parţial and total edentation provisionally prosthetic loaded and tested for a period of 30-45 days. În the clinical cases taken în treatment the method with adjustable simulator and facial arch (7 cases), the method with average simulator (10 clinical cases) and the simple simulator method (8 clinical cases) were used.